ANATOMICAL STUDY OF THE POSTEROLATERAL LIGAMENT COMPLEX OF THE KNEE: LCL AND POPLITEUS TENDON - MARCEL FARACO SOBRADO; CAMILO PARTEZANI HELITO; LUCAS DA PONTE MELO; ANDRE MARANGONI ASPERTI; RICCARDO GOMES GOBBI; FABIO JANSON ANGELINI (Acta Ortopédica Brasileira, 2021)
ABSTRACT Objective: To analyse the distances between the femoral insertions of the popliteus tendon (PT) and the lateral collateral ligament (LCL) through dissections of cadaveric specimens in a mixed population. Methods: Fresh cadavers were dissected, and the anthropometric data of all specimens were recorded. The distances from the origin of the PT to the LCL in the femoral region and the diameter of each structure were measured using a digital calliper. Results: In total, 11 unpaired knees were dissected, eight men and three women, with an average age of 71.5 ± 15.2 years, weight of 57.2 ± 15.6 kg, and a mean height of 170.5 ± 8.2 cm. The distance from the center of the femoral footprint of the LCL to the PT was 10.0 ± 2.4 mm. The distances between the edges closest to each other and those more distant from each other were 3.1 ± 1.1 mm and 16.3 ± 2.4 mm, respectively. Conclusion: The distance between the midpoints of the PT and the LCL in our mixed population is smaller than the distances often reported in the literature. PLC reconstruction with separate tunnels for the LCL and PT may not be technically possible for individuals of any population. Level of Evidence III, Diagnostic studies.